Epitaxial Growth of BaBiO3 Thin Films on SrTiO3(001) and MgO(001) Substrates Using Molecular Beam Epitaxy: Controlling the Competition Between Crystal Orientations - Islam Ahmed; Stefan De Gendt; Clement Merckling (Crystals)
BaBiO3 has recently gained significant research attention as a parent material for an interesting family of alloyed compositions with multiple technological applications. In order to grow a variety of structures, a versatile deposition tool such as molecular beam epitaxy must be employed. In this work, the molecular beam epitaxy growth of BaBiO3 on SrTiO3(001) and MgO(001) substrates is studied. When grown by molecular beam epitaxy on SrTiO3(001) or MgO(001) substrates, BaBiO3 is known to have two competing orientations, namely (001) and (011). Characterization of the thin film is carried out by X-ray diffraction, X-ray reflectivity, atomic force microscopy, Rutherford backscattering, and transmission electron microscopy. Pathways to block the growth of BaBiO3(011) and to grow only the technologically relevant BaBiO3(001) are described for both substrates. An understanding of the enabling mechanism of the co-growth is established from an epitaxial point of view. This can be beneficially utilized for the growth of different compositions in the BaBiO3 material family in a more controlled manner.